The Regional Situation in the Middle East: Current State and Prospects for Development - A. Krylov; A. Fedorchenko (Международная аналитика, 2015)
The article analyzes the main trends that determine the dynamics of transformation processes and the future of the entire Middle East region. Projected scenarios are examined through the prism of Russian foreign policy and strategic interests.It has become even more evident that the American scheme of the new world order, including the Middle East, is unviable. Strengthening of Islamic radical organizations and expanded range of their activities were connected with the coming to power of the Obama administration. In Iraq, Syria, the former confrontation has entered a new phase and become even more acute. In 2014, «Islamic State» (ISIS) has begun a largescale expansion, as a result of the bloody battles part of the territory of these countries came under the control of the Islamists. The effectiveness of the fight against the ISIS is due to a combination of political, military, economic and social measures. Furthermore, it should be coordinated internationally. The coordination of anti-terrorist activities of Russia with the countries of East and West can bring positive results.Resolving of the Israeli-Palestinian conflict has reached a deadlock. The fundamental unwillingness of governments, led by Benjamin Netanyahu, to go to any concessions to the Palestinians eventually led to the predictable surge in violence between the conflicting parties in the autumn of 2015, which many political observers and analysts attributed to the beginning of the third intifada.In the depths of the Arabian monarchies there are complex social and economic processes. In the period of generational change in some GCC countries the problem of succession is quite acute. In the south of the Arabian Peninsula an assessment of the current difficult situation in Yemen suggests that the least painful exit for this country is federalization. In the final part of the article the system lag of the region in economic development is considered as a further challenge to the states of the Middle East.